The French system of monetary and credit controls - HODGMAN, D.R. (PSL Quarterly Review, 2014)
The article presents French monetary and credit controls as a coherent system, displays the inner logic of this system and evaluates its implications for policy objectives related to growth, the price level and balance-of-payments. The French system is sufficiently different from other countries in the degree of “socialisation” of credit and direct administrative intervention by the authorities into credit affairs. The effects of traditional operations such as open market purchases cannot be understood in the French environment without a grasp of certain features of French financial institutions. Moreover, the French authorities assign priority to selective credit policy as distinct from general monetary policy and are permitted to intervene in the free play of financial market forces through administrative measures. JEL: E52, E31, F32